2022
DOI: 10.1002/hyp.14532
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of water partitioning in complex urban landscapes with isotope‐aided ecohydrological modelling

Abstract: Urban green space is increasingly viewed as essential infrastructure to build resilience to climate change by retaining water in the city landscape and balancing ecohydrological partitioning into evapotranspiration for cooling and groundwater recharge. Quantifying how different vegetation types affect water partitioning is essential for future management, but paucity of data and the complex heterogeneity of urban areas make water balance estimates challenging. Here, we provide a preliminary assessment of water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 34 publications
2
4
0
Order By: Relevance
“…The actual evapotranspiration estimated within the model (Table S2) was within the range of estimates for previous study sites in Berlin (Gillefalk et al, 2021, 2022; Kuhlemann et al, 2021); however, the water loss estimates were at the low‐end of feasible ranges. The estimates may be lower than expected due to multiple factors, including the lower influence of green space sensitivity due to the calibration bias to blue water fluxes at the sub‐catchment scale, and the differences in model structure on estimation (e.g.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…The actual evapotranspiration estimated within the model (Table S2) was within the range of estimates for previous study sites in Berlin (Gillefalk et al, 2021, 2022; Kuhlemann et al, 2021); however, the water loss estimates were at the low‐end of feasible ranges. The estimates may be lower than expected due to multiple factors, including the lower influence of green space sensitivity due to the calibration bias to blue water fluxes at the sub‐catchment scale, and the differences in model structure on estimation (e.g.…”
Section: Discussionsupporting
confidence: 69%
“…The actual evapotranspiration estimated within the model (Table S2) was within the range of estimates for previous study sites in Berlin (Gillefalk et al, 2021(Gillefalk et al, , 2022Kuhlemann et al, 2021); however, the water loss estimates were at the low-end of feasible ranges.…”
Section: Evaluating Urban Hydrological Processessupporting
confidence: 57%
See 1 more Smart Citation
“…Consequently, more hydrological studies are moving towards integrating a more process-based understanding of the spatio-temporal dynamics of the urban water cycle components across the urban critical zone (Arden et al, 2014 ; Cristiano et al, 2020 ; Gillefalk et al, 2022 ; Salvadore et al, 2015 ). Studies investigating urban catchment hydrology have shown significantly lower water ages (Mean Transit Times – MTTs) and higher fractions of young water than non-urban catchment as a result of artificial storm drainage and reduced recharge and groundwater storage under impervious surfaces (Bonneau et al, 2018 ; Kuhlemann et al, 2022 ; Parajulee et al, 2019 ; Soulsby et al, 2015 ; Stevenson et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Ecohydrological processes in urban green spaces have been investigated across scales, ranging from the street scale (Meili et al, 2020 ), to plot and sub-district level (Gillefalk et al, 2021 , 2022 ) for addressing soil water storage dynamics and evapotranspiration, and integrating specific urban effects on ecohydrological fluxes (Meili et al, 2020 ; Ring et al, 2023 ). Urban impacts on groundwater recharge have also been investigated.…”
Section: Introductionmentioning
confidence: 99%